The Effect of CO2 Injection on Macroalgae Gelidium latifolium Biomass Growth Rate and Carbohydrate Content - Mujizat Kawaroe; Adriani Sunuddin; Dina Augustine; Dea Fauzia Lestari (Marine Science Department Diponegoro University, 2016)
There are many species of macroalga grow in marine ecosystem and potentially as raw material for bioethanol resource. Bioethanol is a conversion result of carbohydrate, one of macroalgae biomass content. The exploration of macroalgae require information about growth rate ability to determine availability in the nature. This research analyze growth rate and carbohydrate content of marine macroalga Gelidium latifolium on cultivation using varied injection of carbon dioxide and aeration. The treatments were control (K), 2000 cc CO2 injection and aeration (P1), 3000 cc CO2 injection and aeration (P2), 2000 cc CO2 injection without aeration (P3), and 3000 cc CO2 injection without aeration (P4). Samples weight were 3 gram in early cultivation on laboratorium scale for 42 days observation. The results showed that the daily growth rate Gelidium latifolium during the study ranged from 0.02-1.06%. The highest daily growth rate was 1.06±0.14% (P2). Carbohydrate yield was 18.23% in early cultivation then 19.40% (K and P2), 20.40% (P1), 16.87% (K3), and 16.40% (P4) after cultivation. The high of carbohydrates value may not guarantee the sustainable Gelidium latifolium biomass utilization as raw material for bioethanol production because of the low growth rate, thus it is necessary to modified and encourage cultivation method effectively. Keywords: CO2 injection, growth rate, carbohydrate, macroalgae, Gelidium latifolium